Investigation on Microstructure and Mechanical Properties of Aluminum reinforced with MWCNT and Nano-SiC (International Journal of Engineering and Computer Science, 2018)
Aluminum is most preferable structural material in the field of automotive and aerospace due to its properties such as strength, corrosion resistance and being light weight. So, to enhance mechanical properties of aluminum, attempts has been made to reinforce it with ceramic materials like Multi walled Carbon Nanotube (MWCNT), Silicon carbide (SiC), separately. This paper focuses on fabrication of Aluminum (Al) with dual reinforcement MWCNT- nanoSiC by powder metallurgy method and study of mechanical properties of composite as well as its microstructure